Longitudinal Estimation of the Clinically Significant Change in the Treatment of Major Depression Disorder - Cañete-Massé, Cristina; Peró-Cebollero, Maribel; Gudayol-Ferré, Esteve; Guàrdia-Olmos, Joan (Frontiers in Psychology, 2018)
Background: Although major depressive disorder is usually treated with antidepressants, only 50% to 70% of the patients respond to this treatment. This study applied Jacobson and Truax’s (1991) methodology (reliable change index - RCI) to a sample of depressive patients being treated with one of two antidepressants to evaluate their functioning and the effect of certain variables such as severity and age. Method: Seventy-three depressive patients medicated with Escitalopram (n=37) or Duloxetine (n=36) were assessed using the Hamilton depression rating scale over a 24-week period. Results: They indicate that the RCI stabilizes in an absolute way starting in week 16, and it is not until week 24 that all of the patients become part of the functional population. We found limited statistical significance with respect to the RCI and the external variables. Conclusions: Our study suggests the need to accompany the traditional statistical methodology with some other clinical estimation systems capable of going beyond a simple subtraction between pre and posttreatment values. Hence, it is concluded that RCI estimations could be stronger and more stable than the classical statistical techniques.